Bioinspired Catalysts: Exceptional High‐Performance of Pt‐Based Bimetallic Catalysts for Exclusive Detection of Exhaled Biomarkers (Adv. Mater. 36/2017). Issue 36 (21st September 2017) - Kim, Sang‐Joon; Choi, Seon‐Jin; Jang, Ji‐Soo; Cho, Hee‐Jin; Koo, Won‐Tae; Tuller, Harry L.; Kim, Il‐Doo
Abstract : Nanofibrous semiconductor metal oxides (SMOs) functionalized by Pt‐based bimetallic catalysts are synthesized by bioinspired protein templates by Il‐Doo Kim and co‐workers in article number1700737 . Pt‐based bimetallic catalysts such as PtPd, PtRh, and PtNi are uniformly functionalized on the surface of the SMO nanofibers. As a result, exceptionally high sensing performance is achieved by selective detection of the biomarker species, such as acetone and hydrogen sulfide, in exhaled breath with potential application in the diagnosis of diseases by analyzing exhaled human breath.